Easy Comfort Food : Simple Recipes for Feel-good Favourites. - Indexer by Shotter Sandra (New York Ryland Peters & Small, 2008)
"Had a tough day at work or just feeling a bit down in the dumps? There's nothing more comforting than good, home-cooked food. Your will find over 100 recipes to satisfy and sooth from Macaroni Cheese to Chocolate Brownies."--Provided by publisher.
Include Colour Illustrations and Index
Designed by Hoyle, Lona
Keywords: Quick and easy cooking -- Comfort food